Órgãos societários na sociedade limitada - Vitale Junior, Ivan Lorena (2005)
ABSTRACT The aim of this paper is to discuss about the partnership organ in the limited partnership, not putting aside the changes that happened with the beginning of the Civil Code of 2002 and the institutional way that the new law caused in these juridical institutes. This kind of partnership has great importance in the Brazilian juridical system as it represents the most used kind of partnership. This paper is divided into three chapters: the fist one characterizes the new administrative structure in the limited partnership as the identification of the new structures with the meaningful changes in the status of the new administrator and the instruments of designation and its new responsibilities, mainly the ultra vires theory. The second chapter discusses about the newness of legislative forecast of the fiscal council to the limited partnership in all its aspects, even if it is a facultative organ. In the last chapter the partnership deliberations were analyzed, mainly the new partner assembly, above all in the partnerships with more than ten partners and the way the legislator wrote down the conduction of this institute. To sum up, the organs are really important in the partnership life so that without them the partnership could not practice the business acts. However, the focus is not the administrative aspects but the juridical ones, the way through the referred organs practice these acts related to the validity and its manifestations.